Characteristics of cortical spreading depression and c-Fos expression in transgenic mice having a mutation associated with familial hemiplegic migraine 2. (October 2020) - Tang, Chunhua; Unekawa, Miyuki; Shibata, Mamoru; Tomita, Yutaka; Izawa, Yoshikane; Sugimoto, Hiroki; Ikeda, Keiko; Kawakami, Kiyoshi; Suzuki, Norihiro; Nakahara, Jin
Background: Cortical spreading depression is thought to be the underlying mechanism of migraine aura. In 2006, three relatives having the point mutation E700K in ATP1A2 exon 15 were diagnosed with familial hemiplegic migraine 2 characterized by complicated forms of aura. Here, we generated a transgenic mouse model having the human E700K mutation in the Atp1a2 orthologous gene. Objective: To investigate the characteristics of cortical spreading depression in a mouse model with E700K mutation in the Atp1a2 . Methods: Cortical spreading depression was induced by applying stepwise increases of KCl concentration or electrical stimulation intensity to C57BL/6J-Tg(Atp1a2*E700K)9151Kwk mice (Tg, both sexes) and corresponding wild-type animals. Under urethane anesthesia, the responsiveness and threshold to cortical spreading depression were examined and the distribution of c-Fos expression, a neuronal activity marker, was immunohistochemically determined. Results: Overall, Tg mice showed significantly faster propagation velocity ( p  < 0.01) and longer full-width-at-half-maximum ( p  < 0.01) than wild-type animals, representing a slower recovery from direct current potential deflection. The cortical spreading depression threshold tended to be lower in Tg, especially in females. c-Fos-positive cells were significantly enhanced in the ipsilateral somatosensory cortex, piriform cortex, amygdala and striatum (each p  < 0.05 vs. contralateral side). Numbers of c-Fos positive cells were significantly higher in the ipsilateral amygdala of Tg, as compared with wild-type animals ( p  < 0.01). Conclusion: The effect of cortical spreading depression may be greater in E700K transgenic mice than that in wild-type animals, while the threshold for cortical spreading depression shows little change. Higher c-Fos expression in the amygdala may indicate alterations of the limbic system in Tg, suggesting an enhanced linkage between cortical spreading depression and amygdala connectivity in familial hemiplegic migraine 2 patients.